Fine Bone China Product using Ceramics Slip Rotary Moulding (CSRM) Technique / Norazne Nasir ...[et al.] - Nasir, Norazne; Saad, Nor Hayati; Sahruddin, Fatin Syafinaz; Ab Wahab, Norrul Hafizan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Bone China is a type of porcelain mainly produced from calcined animal bone. Traditionally, ceramic fine bone china (FBC) products are made by slip casting technique. The traditional technique cannot perform mass production in ceramic industries. Thus, this research focused on improving the productivity of fine bone china product fabrication by introducing a new method called Ceramics Slip Rotary Moulding (CSRM). Basically, the technique of rotary moulding gives high potential for mass production in producing hollow shape green ceramic product. The research compared two formulations of ceramic slip using 100μm and 300μm FBC powders. The slips were prepared and viscosity for both formulations was measured. Specimens for strength test were prepared and using the CSRM green body, the FBC products were produced and sintered. Laboratory test results showed that slip casting with rotary technique required additives to be added in the slip composition to control and gain sufficient coagulation, fluidity and strength to form a green body. The final slip formulation of 78% FBC solid content and 22% water content for both 100μm and 300μm powders required 0.2% dispersant (Acumer 9400) and 0.068% coagulant (Duramax B1020). The amount of additives ensured sufficient fluidity for slip to flow smoothly in the mould during the rotation process and form the FBC green body. The formulation was successfully produced for the Ceramic Slip Rotary Moulding (CSRM) and sufficient green strength was achieved to hold the green body during de-moulding and ready for sintering process.